Hydrostratigraphic Model Analysis Based on Rock Resistivity Data in the Purbalingga Regency Area, Central Java, Indonesia - Sehah, Sehah; Aziz, Abdullah Nur; Pulo Boli, Lusia Silfia; Addailamy, Faizah Ayu; Anas, Almas Atilya Aini; Mubarak, Fuad (Faculty of Geography, Universitas Gadjah Mada, 2025)
The availability of groundwater for irrigation in Purbalingga Regency, requires significant attention since the region has an extensive rice field, necessitating systematic groundwater exploration and the implementation of appropriate management strategies. A geoelectrical resistivity survey has been conducted to investigate groundwater resources and to construct a hydrostratigraphic model that facilitates the interpretation of hydrogeological conditions, including aquifer distribution, groundwater depth, and productive zones. Resistivity data were collected from 16 points distributed across the districts of Kalimanah, Purbalingga, Kemangkon, and Bukateja. The correlation of resistivity logs produced detailed hydrostratigraphic cross-sections, illustrating lithological variations, layer thicknesses, and aquifer distribution. Interpretation down to a depth of 200 m identified two major formations: the Alluvium Formation and the Terrace Formation. The Alluvium Formation, consisting of sandy clay, sand, and clayey sand, exhibits resistivity values ranging from 0.87 to 69.43 Ωm, whereas the Terrace Formation, composed of tuffaceous sandstone, sand, conglomerate, and tuff, with resistivity values between 7.81 and 38.09 Ωm. Hydrostratigraphic modeling indicates that aquifer productivity varies across the study area. Kalimanah District, dominated by low-resistivity deposits (0.87–8.55 Ωm), is interpreted as having the highest aquifer productivity, making it particularly suitable for the development of groundwater-based irrigation. This study introduces a resistivity-based interpretative approach to classify hydrostratigraphic characteristics by correlating resistivity values with local geological conditions.